2018
DOI: 10.1093/inthealth/ihy031
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and negative self-perceptions of young people living with human immunodeficiency virus in Bandung, Indonesia: a case series

Abstract: While these results are preliminary, access to mental health services should be a priority in the clinics that provide antiretroviral therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…A literature review on mental health in Indonesia conducted in PubMed returned 161 studies published between 1949 and 2020. However, only 15 of these studies discussed stigma either directly or in the context of Indonesian mental health services [18,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Among these 15 studies, six discussed stigma in general, consequences of stigma (i.e., "pasung" or confinement), attitudes toward mental health, and perceptions of mental health [18,30,31,[41][42][43].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review on mental health in Indonesia conducted in PubMed returned 161 studies published between 1949 and 2020. However, only 15 of these studies discussed stigma either directly or in the context of Indonesian mental health services [18,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Among these 15 studies, six discussed stigma in general, consequences of stigma (i.e., "pasung" or confinement), attitudes toward mental health, and perceptions of mental health [18,30,31,[41][42][43].…”
mentioning
confidence: 99%
“…However, only 15 of these studies discussed stigma either directly or in the context of Indonesian mental health services [18,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Among these 15 studies, six discussed stigma in general, consequences of stigma (i.e., "pasung" or confinement), attitudes toward mental health, and perceptions of mental health [18,30,31,[41][42][43]. Previous investigations of stigma in Indonesia mainly examined personal stigma, with a focus on the perceptions of those with mental illness and their families, how they respond to stigmatization in their lives, and the impact of stigma on access to mental health facilities or treatment [18,[20][21][22][23]44].…”
mentioning
confidence: 99%
“…It is possible that the persistence of depressive symptoms is related to stigmatisation or lack of social support experienced by PLHIV, even in the context of effective ART treatment. A recent case series of young PLHIV in Indonesia revealed that stigma and negative self-perception persists, and a large number of participants felt that they did not deserve to live (45%) or felt completely worthless (64%) [27]. PLHIV might also experience stigma in medical facilities, where a high rate of HIV-related stigma has been reported, such as among Indonesian nurses [28].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian terkait stigma di Indonesia menemukan beberapa bentuk stigma yang diterima ODHA yaitu berupa penolakan, harga diri rendah/persepsi diri yang negatif, pelecehan verbal, isolasi sosial, dan ketakutan. Bahkan keberadaan stigma ini membuat 45% dari mereka merasa tidak layak untuk hidup dan 64% merasa tidak berharga 6,7 .…”
Section: Pendahuluanunclassified